Análise acerca das respostas específicas do terapeuta para a modificação de padrões de comportamentos antissociais - Gouveia, Michele de Andrade (2018)
This paper aimed to replicate Rocha´s study about psychotherapy with young offenders. It analyzed the aspects of the therapeutic process in forensic practices based on Behavior Analysis principles; examined the therapist's specific answers to antisocial behavior patterns; it attempted to trace the interventions that are most used by the therapist, according to the Multidimensional System for Categorization of Behaviors in Therapeutic Interaction (SiMCCIT); and it identified which of the therapist's abilities were associated with clinical changes to reduce antisocial behaviors and increase prosocial behaviors. We used the Parenting Style Inventory (PSI) to categorize the participants; the Youth Self-Report – YSR; and also, a checklist created by the researcher, based on the DSM-5 diagnosis criteria, to evaluate behavioral patterns. Three teenagers undergoing a social-educational confinement measure were submitted to the psychotherapeutic process of behavior analysis. The therapy sessions of a teenager diagnosed with Antisocial Personality Disorder were selected to be analyzed during the study. Amongst the thirteen sessions, the first, middle, and last sessions were chosen for statistical analysis. The psychotherapy sessions were recorded in audio, transcribed, and analyzed according to the client's behavior categories related to the antisocial behavior patterns. The categories were: a) hostilizing, b) lying, c) blaming others, d) self-manifesting, c) expressing positive feelings and f) expressing genuine regret. The results show that, throughout the process, there were changes in the client’s antisocial behavior pattern, as well as an increase in the pro-social behaviors. However, these changes were not significant during the three analyzed sessions. We verified that the teenager's hostilizing and blaming others behaviors decreased, and their lying behavior did not vary. Regarding pro-social behaviors, the teenager's self-manifesting behavior did not increase, as well as expressing positive feelings. The only increased behavior was the genuine regret one. Concerning the therapist's behavior, the ones who showed more vulnerability during the sessions and tend to be associated with changes in the client's behavior were a) interpreting, b) asking for reflection, c) empathy, d) facilitation, e) recommendation, f) disapproval and g) other verbalization. The study suggests more analysis of a greater number of sessions to investigate if there will be significant changes in a case of Antisocial Personality Disorder.